Cyclic and Torsional Fatigue Resistance of Reciprocating Single Files Manufactured by Different Nickel-titanium Alloys - Alcalde, Murilo P.; Tanomaru-Filho, Mario [UNESP]; Bramante, Clovis M.; Duarte, Marco Antonio H.; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Camilo-Pinto, Jader [UNESP]; Reis So, Marcus Vinicius; Vivan, Rodrigo Ricci (Elsevier B.V., 2017)
Introduction: The aim of this study was to evaluate the cyclic and torsional fatigue resistance of the following reciprocating single-file systems: ProDesign R 25.06 (Easy Equipamentos Odontologicos, Belo Horizonte, Brazil), Reciproc R25 (VDW GmbH, Munich, Germany), and Unicone L25 (Medin SA, Nove Mesto in Morave, Czech Republic). Methods: Sixty instruments of the Pro Design R, Reciproc R25, and Unicone L25 systems (n = 20) were used. Cyclic fatigue resistance was tested measuring the time to failure in an artificial stainless steel canal with a 60 angle and a 5-mm radius of curvature (n = 10). Torque and angle of rotation at failure of new instruments (n = 10) in the 3 mm from the tip portion were measured during torsional testing according to ISO 3630-1. The fractured surface of each fragment was examined by scanning electron microscopy. Data were analyzed using 1-way analysis of variance and Tukey tests, and the level of significance was set at 5%. Results: The cyclic fatigue resistance values of ProDesign.R 25.06 were significantly higher than the other groups (P < .05). Reciproc R25 showed higher fatigue resistance than Unicone L25 (P < .05). In relation to the torsional test, the ProDesign R 25.06 and Unicone L25 systems showed higher angular rotation until fracture than Reciproc R25 (P <.05). However, Reciproc R25 and Unicone L25 showed higher torque load than ProDesign R 25.06 (P <.05). Scanning electron microscopic analysis showed similar and typical features of cyclic and torsional failure for all instruments tested. Conclusions: ProDesign R presented the highest cyclic fatigue resistance and angular rotation to failure compared with Reciproc and Unicone. However, Reciproc showed higher torsional strength to failure.
Keywords: Cyclic fatigue; nickel-titanium; reciprocating systems; torsional resistance